2007
DOI: 10.1089/neu.2007.0382
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Magnetic Resonance Imaging at 1.5 and 3 Tesla for the Evaluation of Traumatic Microbleeds

Abstract: Traumatic microbleeds (TMBs) can be regarded as a radiological marker of diffuse axonal injury (DAI). We sought to investigate the impact of the field strengths on the depiction of TMBs by T2*-weighted gradient echo magnetic resonance imaging (MRI). By the use of comparative MRI of 14 patients (age range, 22-62 years) on 1.5- and a 3 T (Tesla) systems at a median time interval of 61 months after traumatic brain injury (TBI), we found 239 (range 0.5-48.5, median 7.5) TMBs at 1.5 T, and 470 (range 2-118, median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(58 citation statements)
references
References 14 publications
2
53
0
3
Order By: Relevance
“…[2][3][4] Using a custom three dimensional T2* sequence on a 1.5T MRI, which detects MBs with nearly two times the sensitivity of conventional two-dimensional T2* imaging; however, the Rotterdam study recently reported a much higher prevalence in the general population of 23.5%. 10 In the present study, using 3T MRI, which in turn has greater sensitivity than 1.5T MRI, 22 we observed a prevalence of 5% in our studied population free from a history of stroke. These differences in prevalence might be explained by differences in the clinical background of the study populations, particularly with regard to the ratio of hypertensive patients, which was 71.9% in the Rotterdam study compared with 56.2% in the present study.…”
Section: Discussionsupporting
confidence: 40%
“…[2][3][4] Using a custom three dimensional T2* sequence on a 1.5T MRI, which detects MBs with nearly two times the sensitivity of conventional two-dimensional T2* imaging; however, the Rotterdam study recently reported a much higher prevalence in the general population of 23.5%. 10 In the present study, using 3T MRI, which in turn has greater sensitivity than 1.5T MRI, 22 we observed a prevalence of 5% in our studied population free from a history of stroke. These differences in prevalence might be explained by differences in the clinical background of the study populations, particularly with regard to the ratio of hypertensive patients, which was 71.9% in the Rotterdam study compared with 56.2% in the present study.…”
Section: Discussionsupporting
confidence: 40%
“…If 3-T MRI, which is superior to the 1.5-T MRI that was used, had been performed, the frequency of new-EMBs might have increased. 41 Fourth, CT scans were not performed. It is questionable whether CT can detect new-EMBs after tPA infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Standard T2-weighted, T2 FLAIR, and T2*-weighted gradient-recalled echo (GRE) imaging methods often detect small lesions missed on CT. The sensitivity of these methods increases with increasing magnetic field strengths; for example, 3T T2* GRE detects twice as many tiny (several millimeter) parenchymal hemorrhages (sometimes referred to as ''microbleeds'' (9)) as at 1.5T (10). As good as these methods are, there are more advanced MRI methods, yet to be commonly practiced, that offer more sensitive measures of blood products (using susceptibility weighted imaging [SWI]), blood flow and perfusion (using perfusion weighted imaging [PWI]), microstructural white matter (WM) tract integrity (using diffusion tensor imaging), metabolic activity (using MR spectroscopy), and hemodynamic brain function (using fMRI).…”
Section: The Role Of Mrimentioning
confidence: 99%
“…SWI uses not only the magnitude component of the T2* data but also the phase information to enhance contrast and better reveal small hemorrhages. Generally imaging at higher fields such as 3T affords twice the sensitivity to blood products in comparison to 1.5T when using gradient echo imaging (10).…”
Section: Conventional Mri Techniquesmentioning
confidence: 99%